Results of Study of Special Competence of Special Subjects Lecturers in Higher Military Educational Institutions - Rybchuk, Oleh (Journal of Education, Technology and Computer Science, 2019)
The article deals with the essence of special competence of lecturers of special subjects in higher military educational institutions as a multidimensional integral formation, which is a structural complex of professional qualities, abilities and approving of a lecturer as a pedagogic activity subject, that enable him/her to realize successfully certain pedagogic functions as a pedagogic activity subject in the military education system. There were substantiated and experimentally verified the organizational and pedagogic conditions increasing the productivity of development of special subjects lecturers' special competence.